2004
DOI: 10.1007/s11199-004-0724-z
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Is Gender a Factor in Mathematics Performance Among Nigerian Preservice Teachers?

Abstract: The mathematics performance of graduating preservice teachers over a period of 3 years was examined for gender differences. Data were drawn from students' (170 men and 202 women) final year results from a College of Education in Nigeria. Findings revealed that the gender gap in mathematics achievement among the sample data could be disappearing. This is a source of hope for the country because results such as those reported here are contrary to the general Nigerian stereotypical belief about men's and women's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
(20 reference statements)
5
13
1
Order By: Relevance
“…Thus, while gender differences in mathematical proficiency were not significant, gender difference in performance in mathematics in this study was statistically significant. The non-significant gender differences in mathematical proficiency on one hand were in agreement with previous study findings (Arigbabu & Mji, 2004;Awofala & Anyikwa, 2014;Fatade, Nneji, Awofala & Awofala, 2012) in advanced mathematics and numeracy among preservice mathematics teachers and adult learners but ran contrary to other previous findings (Awofala, 2008a;Awofala, 2008b;Awofala, 2010;Awofala, 2011;Akinsola & Awofala, 2009;Ozofor, 2001;Ogunkunle, 2007) which revealed the existence of significant gender differences in mathematics. On the other hand, the significant gender effect on secondary students" performance in mathematics re-echoed the dwindling parlance that males were better in mathematics than females.…”
Section: Research Question Foursupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, while gender differences in mathematical proficiency were not significant, gender difference in performance in mathematics in this study was statistically significant. The non-significant gender differences in mathematical proficiency on one hand were in agreement with previous study findings (Arigbabu & Mji, 2004;Awofala & Anyikwa, 2014;Fatade, Nneji, Awofala & Awofala, 2012) in advanced mathematics and numeracy among preservice mathematics teachers and adult learners but ran contrary to other previous findings (Awofala, 2008a;Awofala, 2008b;Awofala, 2010;Awofala, 2011;Akinsola & Awofala, 2009;Ozofor, 2001;Ogunkunle, 2007) which revealed the existence of significant gender differences in mathematics. On the other hand, the significant gender effect on secondary students" performance in mathematics re-echoed the dwindling parlance that males were better in mathematics than females.…”
Section: Research Question Foursupporting
confidence: 88%
“…Second, some studies showed significant gender difference in mathematics achievement in favour of females (Ozofor, 2001;Ogunkunle, 2007). Third, there are studies that exhibit no significant effect of gender on achievement in mathematics (Arigbabu & Mji, 2004;Fatade, Nneji, Awofala & Awofala, 2012;Awofala & Anyikwa, 2014). While the first and the second categories suggest the existence of differential experiences of boys and girls within and outside the mathematics classroom the third category has come up with the conclusion that gender differences in achievement in mathematics are disappearing.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported significant main effect of gender on students' achievement/performance in mathematics. The present finding failed to support the work of researchers who believed that gender stereotyping was declining in the Nigerian educational system (Fatade, Nneji, Awofala, & Awofala, 2012;Arigbabu & Mji, 2004). The present result was in support of the work of researchers who had established gender differences in achievement in mathematics (Awofala, 2008;Awofala, 2017a).…”
Section: Main Effect Of Gender On Students' Achievement In Algebracontrasting
confidence: 86%
“…Evidence suggests that there was a significant relationship between gender and achievement in mathematics (Akinsola & Awofala, 2009;Awofala, 2011;Awofala, 2010;Fatade, Nneji, Awofala, & Awofala, 2012;Ogunneye, 2003). Contrastingly, some researchers (Abakpa & Iji, 2011;Agommuoh & Nzewi, 2003;Arigbabu & Mji, 2004) had observed no significant effect of gender on students' achievement in mathematics thus concluding that gender differences in achievement/performance might be disappearing (Awofala, Arigbabu & Awofala, 2013). Hydea and Mertzb (2009) revealed that girls have reached parity with boys in mathematics performance, including at high school where a gap existed in earlier decades and affirmed that girls are doing better than boys even for tasks that require complex problem solving.…”
Section: Introductionmentioning
confidence: 96%
“…This finding supports the findings of some scholars like Ogunyemi (1994), and Akinbote et al (2001) that there existed no significant differences between male and female pupils in their learning outcomes in the various school subjects. The present study result of no gender differences in achievement in HIV/AIDS education supported the work of researchers who believed that gender stereotyping could be waning in the Nigerian educational system (Fatade, Nneji, Awofala, & Awofala, 2012; Arigbabu & Mji 2004). However, the result was at variance with the findings of some previous studies Awofala, 2007) that reported significant main effect of gender on students' performance in science and mathematics but agreed with some others (Awofala, 2011 b).…”
Section: Discussionsupporting
confidence: 87%